Tratamiento quirúrgico de la periodontitis en un paciente con obesidad. Reporte de caso - Ramírez Guillen, Jesús Abel (2021)
Clinical case: 39-year-old female patient with class 1 obesity and generalized periodontitis diagnosis, attended the Postgraduate Periodontology program to reduce “bleeding from her gums”. The clinical examination revealed generalized inflammation of the gingival margin and interdental papillae, an average probing depth of 3.8 mm, an average clinical attachment loss of 3.9 mm and class 1 furcation lesions. A mechanical periodontal treatment was planned, showing improvement in the clinical parameters after six months, however, the periodontal pockets persisted, for which resective surgical periodontal therapy was indicated through modified Widman flaps. With a two-year follow-up, periodontal health was maintained with a mean probing depth of 2 mm, bleeding on probing of 6% and oral hygiene index of 11%, as well as presenting areas with probing depth> 3 mm but without bleeding on probing in these areas. It is concluded that after resective surgical periodontal therapy, the periodontal parameters of gingival inflammation, depth to probing and bleeding on probing were reduced and controlled in a patient diagnosed with class 1 obesity and generalized periodontitis.